2023
DOI: 10.2514/1.b38501
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on Fully Coupled Combustor–Turbine Interactions

Abstract: Combustor–turbine interactions are investigated by modeling the unsteady flowfields inside a realistic combustor and high-pressure turbine configuration from the Energy Efficient Engine program. We perform three-dimensional unsteady simulations to capture a liquid-spray fuel/air combustion and relative motions between the combustor and turbine using the Open National Combustion Code. To understand combustor–turbine interactions, we perform both sequential single-component simulations (step 1: [Formula: see tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…They observed that whilst the vane potential effect is weak, the clocking significantly affects the van temperature and flow conditions. Miki et al [13] compared the sequential single-component simulation method against the fully coupled simulation method for a combustor-turbine system. Although the mean combustor flowfields were similar between the two methods, there was a significant difference in the hot-streak distributions.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that whilst the vane potential effect is weak, the clocking significantly affects the van temperature and flow conditions. Miki et al [13] compared the sequential single-component simulation method against the fully coupled simulation method for a combustor-turbine system. Although the mean combustor flowfields were similar between the two methods, there was a significant difference in the hot-streak distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Results from that analysis were discussed in Section 3.1. Miki et al [205] compared results obtained from the fully coupled and the decoupled simulations of the "Energy Efficient Engine" combustor [206] and turbine [207], and an integrated simulation using high-fidelity methods. Results obtained with the decoupled simulation were considered inaccurate, while fully coupled methods demonstrated their superior ability to capture flow physics, although only the integrated simulation individuated a low-pressure region downstream of the first-stage vane.…”
mentioning
confidence: 99%